PLANT BREEDING TO DISEASE RESISTANT WITH BIOTECHNOLOGY TECHNIQUE - Kristamtini Kristamtini (Agros Journal of Agriculture Science, 2005)
Conventional plant breeding for disease resistant have been conducted for quite a long time has some limitation because of limited field selection, require a long time to conduct, cross incompatibility, interspesific crossing. So to adopt a need a new technique to stimulate agricultural technology for disease resistant. This technique biotechnology were plant tissue culture to disease resistant (meristem culture, callus culture, cell culture), mutation isolated to disease resistant from cell culture, protoplast fusion, anther culture, embryo rescue and genetic engineering to disease resistant.